THE EFFECT OF PREGNANCY AND CHILDBIRTH HEALTH EDUCATION ON REDUCING ANXIETY OF THIRD-TRIMESTER PREGNANT WOMEN - Novi Yulianti; Hafizah Che Hassan (Yayasan Media Utama Sains, 2024)
Background: Physiological and psychological anxiety significantly impacts maternal and fetal health. Lack of knowledge about pregnancy and childbirth dominates the causes of anxiety. This study investigated whether third-trimester pregnancy anxiety can be reduced by receiving health education about pregnancy and labor. Methods: Quasi-experimental quantitative research was conducted using a design consisting only of before and after tests. The sample consisted of 64 third-trimester samples selected using a purposive sampling approach. The measuring instrument used was the Pregnancy-Related Anxiety Questionnaire-R2. Univariate analysis tests and bivariate analysis were conducted to see the significance and differences before and after treatment using paired t-tests. Results: It was found that most of the subjects were primigravida 36 (56.2%) respondents, the majority were aged 20-35 years 47 (73.4%), and the majority of education was Bachelor 27 (42.2%), and the majority of economic income < regional minimum wage. Most pregnant women experienced anxiety before childbirth in the moderate category 35 (54.7%) respondents. Demographic factors of education, parity, and economic income have a significant relationship with a p-value of 0.000, but age has no relationship with the incidence of anxiety. Conclusion: The difference between pre and post by looking at the two-tailed sig number with a result of 0.000 <0.05, the Confidence interval value of the difference is lower 0.900 and upper 1.099. In the t-test, the sig value. (2-tailed) of 0.000 (<0.05), which shows that health education about pregnancy and childbirth reduces the anxiety of third-trimester pregnant women facing labor.